Charismatic Children: Heredity, Environment and ICTs - Vouglanis, Taxiarchis; Driga, Anna Maria; Drigas, Athanasios (Technium Sustainability, 2022)
The aim of this article is to investigate whether or not charisma in children is considered inherited or not. There is no generally accepted definition of the gifted-charismatic child. However, various definitions of intellectual superiority include either general high capacity or high special capacity. The charisma of a child becomes apparent early in life. It can be considered as a biologically rooted label for a high level of intelligence, which shows an advanced and accelerating development of functions within the brain that allow its more efficient use. However, an interaction between the environment and the genetic framework creates intelligence, even the perception of reality. It is often difficult to separate the influences of genetics and the environment on human traits. Genetic traits do not appear instantly at the time of birth; instead, they tend to follow inherent epigenetic development pathways. Charismatic children develop asynchronously: their minds are often more ahead of their natural development and specific cognitive and emotional functions often develop differently at different stages of development. Finally, both the genetic material of the child, the environment within which the child grows and the ICTs usage and training, contribute to the development of charisma.